Radiological-Pathological Correlation in Plasmablastic Lymphoma in an Immunocompromised Patient - A. Moramarco; M. Marenco; M. La Cava; A. Lambiase (Case Reports in Ophthalmological Medicine)
Plasmablastic lymphoma (PBL) is a malignant, rare, and aggressive form of non-Hodgkin’s lymphoma with poor response to treatment that most commonly involves the oral mucosa of immunodeficient patients. The orbit might be primarily or secondarily involved; on the other hand other pathological conditions, i.e., fungal infections, may localize in the orbit in both immunocompromised patients and drug user, which might have similar radiological features. We describe the clinical, radiological, and pathological features of an orbital plasmablastic lymphoma (PBL) in an immunocompromised HIV positive drug user patient.